Opportunities for the Financial and Economic Transformation of the Czech Republic - Konečná, Veronika; Teplý, Petr, 1977-; Škrabka, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis explores the potential of tokenization and programmable money to enhance the Czech Republic’s financial system and stimulate economic growth. It examines how tokenization could facilitate more efficient capital raising for the government and how programmable payments might be utilized within public and private sectors. Given the Czech Republic’s current lag behind other European nations in digital innovation, the thesis investigates whether adopting forward-thinking digital approaches could position the country as a regional leader in financial technology. The analysis highlights a significant gap in the adoption of Real-World Asset (RWA) tokenization and evaluates the transformative impact such technologies could have on the economy. It is estimated that implementing a fully digitalized Digital Payment Infrastructure (DPI) could generate savings ranging from 0.5 % to 5 % of GDP—equivalent to CZK 38.1 billion to CZK 380.9 billion annually. Furthermore, the thesis discusses how the Czech financial system’s dependence on traditional banking institutions inhibits innovation. Major banks often limit technological investment and tend to acquire fintech startups to neutralize competitive threats, thereby slowing the broader adoption of cutting-edge financial technologies like tokenization.
Vedoucí práce: Petr Teplý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses